The merger rate of galaxies in the Illustris simulation: a comparison with observations and semi-empirical models - Rodriguez-Gomez, Vicente; Genel, Shy; Vogelsberger, Mark; Sijacki, Debora; Pillepich, Annalisa; Sales, Laura V.; Torrey, Paul; Snyder, Greg; Nelson, Dylan; Springel, Volker; Ma, Chung-Pei; Hernquist, Lars (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We have constructed merger trees for galaxies in the Illustris simulation by directly tracking the baryonic content of subhaloes. These merger trees